Segmented assimilation on the ground: the new second generation in early adulthood - Portes, Alejandro; Kelly, Patricia Fernández; Haller, William (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
We review the literature on segmented assimilation and alternative theoretical models on the adaptation of the second generation; summarize the theoretical frame work developed in the course of the Children of Immigrants Longitudinal Study; and present evidence from its third survey in South Florida bearing on alternative hypotheses. We find that the majority of second generation youths are moving ahead educationally and occupationally, but that a significant minority is being left behind. The latter group is not distributed randomly across nationalities, but corresponds closely to predictions based on immigrant parents’ human capital, family type, and modes of incorporation. While it is clear that members of the second generation, whether successful or unsuccessful will assimilate – in the sense of learning English and American culture – it makes a great deal of difference whether they do so by joining the main stream middle-class or the marginalized, and largely racialized, population at the bottom. Narratives drawn from the ethnographic module accompanying the survey put into perspective quantitative results and high light the realities of segmented assimilation as it takes place today in U.S. society.